A sulfur vacancy-rich ferrous disulfide modified enteromorpha biochar composite material, a preparation method thereof and application of the composite material in degrading antibiotics

CN122875256APending Publication Date: 2026-10-09FIRST INSTITUTE OF OCEANOGRAPHY MNR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611334568.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

目前,将硫空位工程与浒苔生物炭负载FeS2相结合,构建高效、稳定、抗干扰的复合催化材料,并用于水体抗生素污染修复的研究较少,缺乏可控的制备工艺与清晰的作用机制

Benefits of technology

(1)本发明通过球磨与氮气退火耦合处理,在FeS2中成功构筑高浓度VS,VS作为核心活性位点,显著调控电子结构、增强PMS吸附亲和力、降低活化能垒、促进界面电子转移,高效生成以单线态氧(1O2)为主的活性物种,使复合材料具备远超纯生物炭与未改性FeS2的催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875256A_ABST
    Figure CN122875256A_ABST
Patent Text Reader

Abstract

This invention relates to the field of marine biological resource utilization and water pollution remediation technology, and discloses a sulfur-vacancy-rich ferrous disulfide-modified *Ulva prolifera* biochar composite material, its preparation method, and its application in degrading antibiotics. This invention successfully introduces sulfur vacancies by ball milling FeS2 with BC and annealing under a nitrogen atmosphere, obtaining a sulfur-vacancy-rich material (V... S This invention relates to a composite material of *Ulva prolifera* biochar modified with iron disulfide. The composite material can efficiently activate persulfate, achieving rapid and efficient removal of antibiotics such as tetracycline from water. S As the core active site, it can significantly regulate the electronic structure of FeS2 and reduce the activation energy barrier. The composite material has the characteristics of large specific surface area, abundant active sites, fast electron transfer, excellent stability and reusability, and strong resistance to water quality interference. Moreover, the preparation process is controllable, the raw material cost is low, and it is environmentally friendly, making it suitable for large-scale remediation applications of antibiotic pollution in water bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine biological resource utilization and water pollution remediation technology, specifically to a sulfur-vacancy-rich ferrous disulfide (FeS2)-modified Ulva prolifera biochar composite material, its preparation method, and its application in the degradation of antibiotics in water bodies by activated persulfate. It can efficiently remove antibiotic pollutants such as tetracycline (TC) and is suitable for the safe remediation of aquaculture wastewater and natural water bodies. Background Technology

[0002] In recent years, the explosive proliferation of the large marine algae *Ulva prolifera* has triggered green tide disasters. Simultaneously, the overuse of antibiotics in mariculture has led to increasingly serious residual pollution, threatening ecological security and human health. Biochar, due to its wide availability of raw materials, well-developed pores, and environmental friendliness, has become an ideal carrier for pollution remediation. *Ulva prolifera*, as a waste biomass, possesses natural advantages for preparing high-performance biochar. However, pure biochar has insufficient active sites and limited catalytic capacity, while ferrous disulfide (FeS2) has good electron transport and persulfate activation properties, but it is prone to aggregation and its activity is difficult to regulate.

[0003] Sulfur vacancies, as typical lattice defects, can effectively modulate the electronic structure of metal sulfides, enhance adsorption capacity, lower reaction energy barriers, and significantly improve catalytic activity. Currently, there is limited research on combining sulfur vacancy engineering with FeS2 supported on Ulva prolifera biochar to construct efficient, stable, and interference-resistant composite catalytic materials for the remediation of antibiotic pollution in water bodies, lacking controllable preparation processes and clear mechanisms of action. Therefore, developing a FeS2 / Ulva prolifera biochar composite material with controllable sulfur vacancies, simple preparation, and excellent remediation performance has significant application value. Summary of the Invention

[0004] The technical problem to be solved by this invention is to address the shortcomings of existing technologies by providing a sulfur-vacancy-rich ferrous disulfide-modified *Ulva prolifera* biochar composite material, its preparation method, and its application in antibiotic degradation. The composite material of this invention constructs sulfur vacancies (S2) through ball milling and annealing. V This material can efficiently activate persulfate (PMS) to achieve rapid and efficient degradation of antibiotics such as tetracycline (TC). The composite material has a large specific surface area, abundant active sites, excellent cycle stability and anti-interference ability, and its preparation process is simple and low-cost. It can be used as a raw material for the resource utilization of waste *Ulva prolifera*, making it suitable for large-scale production applications.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: One objective of this invention is to provide a method for preparing a sulfur-vacancy-rich ferrous disulfide-modified *Ulva prolifera* biochar composite material, comprising the following steps: preparing *Ulva prolifera* biochar (BC), synthesizing FeS2 using a hydrothermal method, ball milling and compounding FeS2 with BC, and then annealing under a nitrogen atmosphere to introduce sulfur vacancies, thereby obtaining the sulfur-rich composite material. V FeS2 modified Ulva prolifera biochar composite material (V S -FeS2 / BC).

[0006] In the above technical solution, the specific operation process for preparing BC is as follows: Fresh seaweed is collected, washed with ultrapure water to remove surface impurities, freeze-dried overnight at -48℃, then pulverized into fine powder by ball milling, and sieved to obtain seaweed powder with a particle size of 100μm. The seaweed powder is soaked in 0.5~1M dilute hydrochloric acid (1.0mol / L dilute hydrochloric acid is used in this embodiment) at a solid-liquid ratio of 1g:10mL, and stirred and acid-washed at room temperature for 2h; filtered, and washed with ultrapure water until the pH of the filtrate is 7 and the conductivity is less than 20μS·cm. -1 Freeze-dry overnight at -48℃ (holding temperature for 3-4 hours), cold trap temperature -55℃, chamber vacuum degree 10-30Pa, total freeze-drying time of sublimation-desorption 22 hours, and the moisture content of the material at the end of drying is controlled below 3%; acid-washed seaweed powder is obtained. The acid-washed seaweed powder is placed in a tube furnace and heated to 400℃ at 10℃ / min, calcined at a constant temperature for 2 hours, and then cooled to obtain BC.

[0007] In the above technical solution, the hydrothermal preparation of FeS2 is specifically carried out as follows: 5.0 mmol of ferrous sulfate heptahydrate is dissolved in 50.0 mL of ultrapure water, 0.4 g of polyvinylpyrrolidone and 30.0 mL of saturated polyvinyl alcohol solution are added, and the mixture is magnetically stirred for 30 min. While stirring, about 10.0 mL of 1.0 M NaOH is slowly added, and 7.5 mmol of sodium sulfide is dissolved in 20.0 mL of ultrapure water and slowly added dropwise. After the solution changes color, the pH is precisely adjusted to 8-9. 7.5 mmol of sulfur powder is weighed and added to the mixture, and the mixture is vigorously stirred for 30 min, sonicated for 30 min, and stirred again for 30 min. 0.5 g of ascorbic acid is added. The mixture is transferred to a reaction vessel with a filling rate of 45% and reacted at 180 °C for 12 h. The hydrothermal product is washed three times each with ultrapure water and anhydrous ethanol, and then dried in a 60 °C oven to obtain FeS2.

[0008] In the above technical solution, the ball milling and annealing treatment specifically involves the following steps: FeS2 and BC are ball-milled at a ratio (mass ratio FeS2:BC = 1:2) for 6 hours (ball milling conditions: ball-to-material ratio 20:1, rotation speed 400 r / min). After ball milling, the sample is placed in a tube furnace under a nitrogen atmosphere. The temperature is increased slowly from 0-200℃ to 5℃ / min, which fully removes adsorbed water and organic solvents introduced during ball milling, eliminates internal thermal stress, and prevents FeS2 particles from detaching from the biochar surface. The temperature is then increased rapidly from 200-400℃ to 15-20℃ / min, quickly crossing the critical temperature range for sulfur vacancy generation and creating a large number of bulk sulfur vacancies within the FeS2 lattice, not just surface sulfur vacancies. Finally, the sample is calcined at 400℃ for 2 hours to induce the formation of V. S After cooling, V is obtained. S -FeS2 / BC composite material.

[0009] This invention introduces lattice distortion as a precursor through ball milling, and annealing converts the mechanical distortion into sulfur vacancies in a directional manner, thereby achieving chemical bonding between FeS2 and Ulva prolifera biochar at the interface. This invention achieves the dual effect of creating defects and building a tight heterogeneous interface.

[0010] In the above technical solutions, the washing is performed three times each with ultrapure water and anhydrous ethanol; the drying is performed at 60°C.

[0011] The second objective of this invention is to provide a sulfur-vacancy-rich ferrous disulfide-modified *Ulva prolifera* biochar composite material, prepared by the above-mentioned method. The composite material is a heterogeneous composite material, i.e., VS-FeS2 / BC composite material, formed by loading ferrous disulfide (FeS2) onto the surface of *Ulva prolifera* biochar (BC). The ferrous disulfide lattice contains both surface and bulk sulfur vacancies, and the electron paramagnetic resonance (EPR) shows a sulfur vacancy characteristic signal at g=2.004. The composite material has a mesoporous structure with a specific surface area of ​​21.39 m²·g. -1 The composite material can activate persulfate PMS, and the degradation process uses singlet oxygen. 1 O2 is the main active species, accompanied by sulfate radicals, hydroxyl radicals, and superoxide radicals. The mass ratio of FeS2 to Ulva biochar is 1:2. After five cycles of use, the composite material maintains a tetracycline degradation rate of over 98.96%. It also maintains high catalytic degradation activity in seawater, tap water substrates, and water bodies containing nitrate, sulfate, chloride ions, and humic acid.

[0012] A third objective of this invention is to provide an application of the sulfur-vacancy-rich ferrous disulfide-modified Ulva prolifera biochar composite material in the degradation of antibiotics.

[0013] The fourth objective of this invention is to provide a method for degrading antibiotics using the aforementioned sulfur-vacancy-rich ferrous disulfide-modified Ulva biochar composite material, comprising the following steps: V S -FeS2 / BC composite material is dispersed in water containing antibiotics, and then PMS is added to the system to initiate an oxidation reaction, achieving efficient degradation of antibiotics under normal temperature and suitable pH conditions.

[0014] In the above technical solution, the V S The dosage of FeS2 / BC was 0.3 g / L, the concentration of PMS in the system was 0.3 mM, the antibiotic was TC, the initial concentration of TC was 25.0 mg / L, the initial pH of the reaction was 8, and the degradation time was 120 min.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention successfully constructs high-concentration V in FeS2 through a coupled treatment of ball milling and nitrogen annealing. S V S As the core active site, it significantly regulates electronic structure, enhances PMS adsorption affinity, lowers activation energy barrier, promotes interfacial electron transfer, and efficiently generates singlet oxygen (… 1 The active species, mainly O2, give the composite material catalytic activity far exceeding that of pure biochar and unmodified FeS2.

[0016] (2) V of the present invention S The FeS2 / BC composite material has a large specific surface area, well-developed mesoporous structure, and abundant active sites. It also has excellent cycling stability, with the TC degradation rate remaining at 98.96% after 5 cycles and no significant structural changes. It maintains high efficiency in the presence of tap water, seawater, and common anions and humic acids, and has strong environmental resistance.

[0017] (3) This invention uses marine waste seaweed as a carbon source to realize the resource utilization of green tide algae, reduce material costs and reduce marine environmental hazards; the preparation process is mild and controllable, the process is simple and there is no secondary pollution, which has both environmental and economic benefits and is suitable for large-scale production and actual water body restoration applications. Attached Figure Description

[0018] Figure 1 V prepared in Example 1 of the present invention S Field emission scanning electron microscope (FESEM) image of FeS2 / BC; Figure 2 The X-ray diffraction (XRD) pattern of the sample prepared in Example 1 of this invention, wherein the horizontal axis is 2θ (angle) in degrees; and the vertical axis is intensity in au (absolute unit). Figure 3 The electron paramagnetic resonance (EPR) spectrum of the sample prepared in Example 1 of this invention, wherein the horizontal axis represents magnetic field strength in G (Gauss); and the vertical axis represents EPR (EPR signal) in au (absolute unit). Figure 4 V prepared in Example 1 of this invention S The curve showing the change in antibiotic TC concentration over time during the catalytic degradation reaction of FeS2 / BC is shown, where the horizontal axis represents Time (in minutes) and the vertical axis represents... C t / C 0, C 0 represents the initial concentration of TC before the reaction begins. C t The reaction time is t TC concentration at that time; Figure 5 V prepared in Example 1 of this invention S - The degradation rate of TC by FeS2 / BC during recycling is shown in the curve, where the horizontal axis represents the Cycle (number of cycles) and the vertical axis represents the degradation rate of TC during recycling. C t / C 0, C 0 represents the initial concentration of TC before the reaction begins. C t The reaction time is t TC concentration at that time; Figure 6 V prepared in Example 1 of this invention S -Degradation curves of FeS2 / BC in actual water bodies such as seawater and tap water, Time (in minutes), with the ordinate being... C t / C 0, C 0 represents the initial concentration of TC before the reaction begins. C t The reaction time is t TC concentration at that time; Figure 7 V prepared in Example 1 of this invention S -FeS2 / BC degradation changes in the presence of common heteroions are shown in the bar graph, where the horizontal axis represents Type (heteroion type) and the vertical axis represents Degradation efficiency (degradation rate), in percentage terms. Figure 8 V prepared in Example 1 of this invention S- Degradation curves of FeS2 / BC in ciprofloxacin (CIP), levofloxacin (LEV), methylene blue (MB), and rhodamine B (RhB), where the horizontal axis represents Type (antibiotic or dye type) and the vertical axis represents Degradation efficiency (degradation rate), in units of %. Detailed Implementation

[0019] The following describes in detail the specific embodiments of the technical solution of the present invention, but the present invention is not limited to the following description: Example

[0020] A sulfur-vacancy-rich iron disulfide-modified Ulva prolifera biochar composite material, the preparation method of which includes the following steps: Fresh seaweed was repeatedly washed with ultrapure water to remove surface impurities, then freeze-dried overnight at -48℃, and then pulverized into fine powder using a ball mill. The powder was sieved to obtain seaweed powder with a particle size of 100 μm. The seaweed powder was then soaked in 0.5-1M dilute hydrochloric acid (1.0 mol / L hydrochloric acid was used in this example) at a solid-liquid ratio of 1 g:10 mL, and acid-washed with stirring at room temperature for 2 hours. The solution was then filtered and washed with ultrapure water until the pH of the filtrate was approximately 7 and the conductivity was less than 20 μS·cm⁻¹. The solution was then freeze-dried overnight at -48℃ (holding temperature for 3-4 hours), with a cold trap temperature of -55℃ and a chamber vacuum of 10-30 Pa. The total freeze-drying time for sublimation and desorption was 22 hours, and the moisture content of the material was controlled below 3% at the end of drying. The acid-washed seaweed powder was then obtained. The acid-washed seaweed powder was placed in a tube furnace and heated to 400℃ at a rate of 10℃ / min, then calcined at this temperature for 2 hours. After cooling, BC was obtained.

[0021] (2) Dissolve 5.0 mmol of ferrous sulfate heptahydrate in 50.0 mL of ultrapure water, add 0.4 g of polyvinylpyrrolidone and 30 mL of saturated polyvinyl alcohol solution, and stir magnetically for 30 min; while stirring, slowly add about 10.0 mL of 1.0 M NaOH, dissolve 7.5 mmol of sodium sulfide in 20.0 mL of ultrapure water and slowly add it dropwise. After the solution changes color, adjust the pH to 8-9 precisely; weigh 7.5 mmol of sulfur powder and add it to the mixture, stir vigorously for 30 min, sonicate for 30 min, stir again for 30 min, and add 0.5 g of ascorbic acid; transfer to a reaction vessel with a filling rate of 45%, and react at 180 °C for 12 h; wash the hydrothermal product three times each with ultrapure water and anhydrous ethanol, and dry it in a 60 °C oven to obtain FeS2.

[0022] (3) FeS2 and BC were ball-milled in proportion for 6 hours. After ball milling, the mixture was placed in a tube furnace under a nitrogen atmosphere. The temperature was slowly increased from 0-200℃ to 5℃ / min. In the low-temperature section, the adsorbed water and organic solvent introduced by ball milling were completely removed, and the internal thermal stress of the sample was eliminated to prevent FeS2 particles from falling off the surface of the biochar. The temperature was rapidly increased from 200-400℃ to 15-20℃ / min to quickly cross the critical temperature range for sulfur vacancy generation, creating a large number of bulk sulfur vacancies inside the FeS2 lattice, rather than just surface sulfur vacancies. The mixture was calcined at 400℃ for 2 hours to induce the generation of sulfur vacancies. After cooling, a ferrous disulfide modified Ulva biochar composite material rich in sulfur vacancies was obtained, labeled as V. S -FeS2 / BC.

[0023] In this embodiment, polyvinylpyrrolidone and polyvinyl alcohol are both high molecular weight surfactants / stabilizers / adhesives, and they work synergistically.

[0024] Sodium sulfide: a sulfur source, stabilizes sulfur ions under alkaline conditions, and under acidic conditions... 2- H2S will be generated and escape, leading to failure; the environment needs to be adjusted to be alkaline. A weakly alkaline environment inhibits Fe. 2+ Hydrolysis reduces the formation of Fe hydrides; an alkaline environment is necessary for the disproportionation of elemental sulfur. Excess elemental sulfur: facilitates the conversion to FeS2.

[0025] Ascorbic acid: a strong reducing agent that prevents Fe from being released. 2+ Oxidized to Fe by dissolved oxygen 3+ .

[0026] Performance testing: (1) The V prepared in this embodiment S -FeS2 / BC was characterized by XRD, FESEM, and EPR. See details for the results. Figures 1-3 The results confirmed that FeS2 successfully introduced V S The composite material exhibits a mesoporous structure with a specific surface area of ​​21.39 m². 2 ∙g -1 FeS2 is uniformly dispersed on the BC surface and exhibits excellent electron transport performance.

[0027] (2) V S -FeS2 / BC is used to degrade TC: Add 25 mg / L TC solution to a beaker, then add 0.3 g / L V. S The initial pH was adjusted to 8 using FeS2 / BC and 0.3 mM PMS. The reaction was carried out under magnetic stirring at room temperature. Samples were taken for analysis after 120 min, and the degradation curve was obtained as shown in the figure. Figure 4 The results showed that TC was completely degraded within 120 min, with the pseudo-first-order kinetic constant (…). k obs The value was 0.0381 min. -1Free radical quenching and EPR experiments confirmed that the system uses singlet oxygen ( 1 O2) is the main active species, and SO4· is also present. - 、·OH、·O2-.

[0028] (3) Material cyclic stability test: V S -FeS2 / BC cyclic degradation test was performed according to the degradation conditions in step (2). After each reaction, V was recovered by centrifugation. S -FeS2 / BC was washed several times with ultrapure water and ethanol, dried at 60°C, and reused. A total of 5 cycles were performed. Figure 5 As shown, the TC degradation rate still reached 98.96% after 5 cycles, confirming that V S -FeS2 / BC exhibits excellent reusability.

[0029] Application Example 1: V prepared in Example 1 S -FeS2 / BC composite materials are used to degrade TC in real water bodies such as seawater and tap water. A 25 mg / L TC solution was prepared using tap water and seawater, respectively, and 0.3 g / L of V prepared in Example 1 was added. S The FeS2 / BC composite catalyst was magnetically stirred with 0.3 mM MPMS, and degradation experiments were conducted at room temperature and initial pH=8. Samples were taken at regular intervals, centrifuged, and the TC concentration was measured at 356 nm using a UV-Vis spectrophotometer to calculate the degradation rate. Figure 6 As shown. The results indicate that V S The FeS2 / BC composite catalyst achieved a TC degradation rate of 95.97% in tap water and a degradation rate of 90.19% in seawater, indicating that the composite material still has excellent catalytic activity and anti-interference ability in actual water matrix and has good potential for practical application.

[0030] Application Example 2: V prepared in Example 1 S -FeS2 / BC composite material is used for the degradation of TC in the presence of common heteroions. Prepare Cl-containing - SO4 2- NO3 - (10.0 mM~100.0 mM) and humic acid (HA, 10.0~30.0 mg / L) in a 25.0 mg / L LTC solution were added sequentially, followed by the addition of 0.3 g / L of V prepared in Example 1. S The FeS2 / BC composite material and 0.3 mM MPMS were magnetically stirred and subjected to degradation experiments at room temperature and initial pH=8. TC concentration was measured periodically, and the degradation rate was calculated. Figure 7 As shown.

[0031] The results showed that: Cl - SO4 2- NO3 - It has almost no effect on the TC degradation process; in the presence of HA, the TC degradation efficiency decreases slightly, but still remains above 92%. This indicates that V S The FeS2 / BC composite catalyst maintains high catalytic activity and excellent anti-interference performance even under common conditions where inorganic anions and natural organic compounds coexist.

[0032] Application Example 3: V prepared in Example 1 S -FeS2 / BC composite material applied to the degradation of CIP, LEV, MB, and RhB Prepare 25 mg / L solutions of CIP, LEV, MB, and RhB respectively, and add 0.3 g / L of V prepared in Example 1 to each solution. S The FeS2 / BC composite catalyst and 0.3 mM MPMS were used for degradation experiments at room temperature and initial pH=8 under magnetic stirring. Pollutant concentrations were measured periodically, and the degradation rate was calculated. Figure 8 As shown. The results indicate that V S The FeS2 / BC composite material exhibits excellent degradation effects on a variety of organic pollutants, with a degradation rate of 80.25% for CIP, 87.68% for LEV, 98.10% for MB, and 99.29% for RhB. This indicates that the composite material has good broad-spectrum degradation capabilities and can simultaneously and efficiently remove antibiotic and dye organic pollutants from water.

[0033] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A ferrous disulfide-modified *Ulva prolifera* biochar composite material rich in sulfur vacancies, characterized in that, The composite material is a heterogeneous composite material, namely VS-FeS2 / BC composite material, formed by supporting ferrous disulfide (FeS2) on the surface of Ulva prolifera biochar (BC). The ferrous disulfide lattice contains both surface sulfur vacancies and bulk sulfur vacancies, and the electron paramagnetic resonance (EPR) shows a sulfur vacancy characteristic signal at g=2.

004. The composite material has a mesoporous structure with a specific surface area of ​​21.39 m². 2 ·g -1 The composite material can activate persulfate PMS, and the degradation process occurs using singlet oxygen. 1 O2 is the main active species, accompanied by sulfate radicals, hydroxyl radicals, and superoxide radicals.

2. The composite material according to claim 1, characterized in that, The mass ratio of FeS2 to Ulva prolifera biochar is 1:2; the composite material maintains a tetracycline degradation rate of over 98.96% after 5 cycles of use; It maintains high catalytic degradation activity in seawater, tap water substrates, and water bodies containing nitrate, sulfate, chloride ions, and humic acid.

3. A method for preparing a sulfur-vacancy-rich ferrous disulfide-modified *Ulva prolifera* biochar composite material, characterized in that, The method for preparing the composite material according to any one of claims 1-2 comprises the following steps: Preparation of Ulva prolifera biochar BC: Fresh *Ulva prolifera* was collected, washed with ultrapure water to remove impurities, freeze-dried at -48℃, pulverized and sieved to obtain *Ulva prolifera* powder with a particle size of 100μm; the *Ulva prolifera* powder was acid-washed with 0.5-1mol / L dilute hydrochloric acid at a solid-liquid ratio of 1g:10mL, and stirred at room temperature for 2h; the powder was filtered and washed until the pH of the filtrate was 7 and the conductivity was less than 20μS·cm⁻¹; the powder was freeze-dried again at -48℃ until the moisture content of the material was ≤3%; the material was calcined in a tube furnace at a constant temperature of 400℃ at a rate of 10℃ / min for 2h, and then cooled to obtain *Ulva prolifera* biochar BC; Hydrothermal synthesis of ferrous disulfide FeS2 5.0 mmol of ferrous sulfate heptahydrate was dissolved in 50.0 mL of ultrapure water. 0.4 g of polyvinylpyrrolidone and 30.0 mL of saturated polyvinyl alcohol solution were added, and the mixture was magnetically stirred for 30 min. A 1.0 mol / L sodium hydroxide solution was added dropwise, followed by a 7.5 mmol sodium sulfide aqueous solution, and the pH was adjusted to 8-9. 7.5 mmol of sulfur powder was added, and the mixture was stirred for 30 min, sonicated for 30 min, and stirred for 30 min in sequence. 0.5 g of ascorbic acid was added. The mixture was transferred to a reaction vessel with a filling rate of 45%, and hydrothermally reacted at 180 °C for 12 h. The product was washed three times each with ultrapure water and anhydrous ethanol, and dried at 60 °C to obtain FeS2. Ball milling composite and segmented step annealing: FeS2 and Ulva prolifera biochar BC were ball milled in a mass ratio of 1:2; the powder obtained from ball milling was placed in a tube furnace under nitrogen atmosphere for segmented step annealing, and after cooling, VS-FeS2 / BC composite material was obtained.

4. The preparation method according to claim 3, characterized in that, Freeze-drying conditions: cold trap temperature -55℃, cavity vacuum degree 10-30Pa, total sublimation-desorption drying time 22h.

5. The preparation method according to claim 3, characterized in that, In step (3), the ball milling conditions are: ball-to-material ratio 20:1, rotation speed 400 r / min, and ball milling for 6 hours.

6. The preparation method according to claim 3, characterized in that, In step (3), annealing; slowly increase the temperature at 5℃ / min from 0-200℃; rapidly increase the temperature at 15-20℃ / min from 200-400℃ to induce the generation of bulk sulfur vacancies; calcine at 400℃ for 2 hours.

7. The application of the sulfur-vacancy-rich ferrous disulfide-modified Ulva biochar composite material according to any one of claims 1-2 in the remediation of antibiotic pollutants in water bodies.

8. The application according to claim 7, characterized in that, When the sulfur-vacancy-rich ferrous disulfide-modified Ulva prolifera biochar composite material is used in the remediation of antibiotic pollutants in water bodies, the VS-FeS2 / BC composite material is added to the water containing organic pollutants, followed by the addition of persulfate PMS to initiate an oxidation reaction, achieving the degradation of organic pollutants at room temperature; the organic pollutants include tetracycline, ciprofloxacin, levofloxacin antibiotics, as well as methylene blue and rhodamine B dyes.

9. The application according to claim 7, characterized in that, When treating tetracycline-contaminated water, the composite material dosage was 0.3 g / L, the persulfate PMS concentration was 0.3 mM, the initial tetracycline concentration was 25.0 mg / L, the initial pH of the reaction was 8, and the reaction time was 120 min.

10. The application according to claim 5, characterized in that, The water bodies to be treated are tap water and seawater; NO3 is present in the water bodies. - SO4 2- Cl - When inorganic anions and / or humic acids are present, efficient degradation of organic pollutants can be achieved.